Presentation - Reyes Fernández, Benjamín (2016)
As guest Editors of Actualidades en Psicología, we are pleased to present a selection of scholarly articles focusing on various areas of Health Psychology. The purpose of this special issue is to present some relevant topics for Health Psychology in the region. We have sought, within the call for papers process, to receive manuscripts from Latin America and other regions of the world, with diverse topics and methodological approaches. Six of the ten manuscripts come from research based in Latin America, with the remaining four from European-based scholars.